The common and counter-hegemonic politics : re-thinking social change - Kioupkiolis, Alexandros, 1975- (Edinburgh University Press, 2019)
Alexandros Kioupkiolis re-conceptualises the common in tandem with the political. By engaging with key thinkers of community and the commons, including Nancy, Ostrom, Hardt and Negri, together with poststructuralist conceptions of agonism and hegemony from Mouffe and Laclau, he remedies problematic issues of power relations and division.